Medicinal plants used as antidotes in northern part of Bastar district of Chhattisgarh. - Sinha, M K; Patel, D K; Kanungo, V K (Journal of Ecobiotechnology, 2012)
The present study has been done on the traditional knowledge of the plants, widely used as Antidotes amongst the local peoples of north Bastar region of Chhattisgarh. The survey was conducted in north Bastar region of the Chhattisgarh state and information was collected from people about the plants used as Antidote against the treatment of Snake/Scorpion bite. The study revealed total of 29 species of plants belonging to 20 families widely used as antidote in northern part of Bastar. The plants species were documented on the basis of their phytochemicals and use in Antidote. Maximum of (03) species were belong to the family Asclepiadaceae and (02) each to family Fabaceae , Acanthaceae and Liliaceae. 75.86 % of the observed plants were found to be propagated by their seeds while, 6.89 % by rhizome, 10.34% by stem cutting and 3.44 % each by other plant parts like tuber and bulb. Study also revealed that plants yielding antidotes are propagated and conserved by the local people of northern region of Bastar as they are vital in treatment of snake/scorpion bite.